BIMBINGAN KONSELING PADA MASYARAKAT MULTIKULTURAL - Nurfarida Deliani (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2018)
Indonesia is a multi culture (diversity) country. As a multi culture (diversity) country has two positive and negative side. Multi culture (diversity) country face with specific problems, such as; ethnic, tribe, faith, poverty, etc.  Those problems brings  to the nepotism, collusion, environment destruction, which will lead Indonesia to ruin. Multi culture is a part of culture recognition  cause to emerge the concern for minority to alliance in unity, and accommodate the diversity and human right for all people. Base on those situation, Guidance and counseling should be held by the deliberate multi culture approach so that will reach the optimum result to relieve all people problems.